Comparative study of wax glands in four Meliponini bees (Hymenoptera, Apidae) producing different quantities of wax - Cavalcante, Vagner Melo [UNESP]; Oliveira, Vagner Tadeu Paes de [UNESP]; Cruz-Landim, Carminda da [UNESP] (Fundação Zoobotânica do Rio Grande do Sul, 2000)
The developmental degree of the wax glands was compared in four Meliponini bees, that produce different quantities of wax. The histological data and height average of the wax epithelium during the time in which the maximum production of wax is expected, are in accordance with the rates of wax produced by the species. In Lestrimelitta limao (Smith, 1863) a species which has cleptobiotic habits, and frequently rob wax from the attacked colonies, the height of wax epithelium was the lowest among the studied species. The cells seem to show an abnormal vacuolated cytoplasm, in the phase in which they would be producing wax.
Keywords: Stingless bees; wax glands; development; wax production